Optimizing cucumber growth: integrating smart irrigation with various fertilization strategies in greenhouse conditions - Eser ÇELIKTOPUZ; Müge ERKAN CAN; Halit ERIŞ (Notulae Botanicae Horti Agrobotanici Cluj-Napoca)
Two different irrigations (full irrigation (FI) and 50% deficit irrigation (WS)) and fertilizations (G0 (not applied), G1 (only bottom fertilizer applied), G2 (only chemical fertilizer applied), G3 (bottom fertilizer and animal manure combined), and G4 (which is designed to apply the bottom fertilizer and chemical fertilizer combined)) were assessed in this study, which was carried out between autumn 2020–2021 with the aim of optimal water and nutrient use in cucumber cultivation in a greenhouse. These treatments were examined for their impacts on fruit quality (fruit weight, length, volume, and the total number of fruits), yield, leaf area (LA), irrigation water use efficiency (IWUE), physiological aspects (net photosynthesis (Pn), stomatal conductivity (gs), leaf water potential (Ψl), and nutrient content (nitrogen (N) and potassium (K)). The smart irrigation system that sensed soil moisture and strategically utilized water ensured effective application of a fertilization mechanism that improved crop quality. The FI treatment significantly increased the fruit quality parameters LA, Pn, gs, and Ψl compared to other treatments, especially when it was combined with the G3 fertilization scheme. The FI treatment also significantly increased fruit yield by 28.3% compared to WS. Additionally, the smart irrigation system saved 20.6% more water under deficit irrigation (WS) and 9.1% more water under full irrigation (FI) compared to Et-based system. Optimally combined strategic fertilization and smart irrigation significantly changed key metrics in growth and development. The results pointed out that technology-driven systems integrated with real-time irrigation data-informed systems are crucial. This work advances sustainable agricultural practices through the integration of effective water management with optimal fertilization. Its findings have significant implications for water-scarce regions, providing a blueprint to improve agricultural productivity while maintaining critical resources.